Malakoplakia mimicking malignant rectal carcinoma with bone erosion in a SLE patient: diagnosis insights from a case report and literature review - Zhang, Lingshu; Zhang, Jingyao; Wen, Ji; Yang, Hang; Sun, Ling; Huang, Tianwen; Sun, Yixin; Jiang, Wei; Tan, Chunyu (Frontiers in Immunology, 2025)
Malakoplakia, an uncommon granulomatous inflammatory disease, is frequently associated with impaired immune function in adults, and its occurrence in patients with systemic autoimmune diseases such as SLE has not been widely studied. The variable clinical manifestations and sometimes non - specific radiological findings of malakoplakia can be misleading, thereby posing a challenge for diagnosis. We report a case of colon and bone malakoplakia mimicking malignant colonic carcinoma in an 18-year-old male with systemic lupus erythematosus (SLE). This case illustrates the diagnostic challenges associated with malakoplakia in patients with SLE. The presence of non-specific symptoms and the mimicry of more common and serious conditions can lead to delayed diagnosis and inappropriate management. Clinicians should be aware of the potential for unusual infectious processes in patients with rheumatic diseases, especially when dealing with abscess-like symptoms. Understanding the pathophysiology and clinical features of malakoplakia in these patients is essential for accurate diagnosis and timely intervention.